W drodze ku synodowi biskupów o młodzieży - Giemza, Bogdan (Studia Pastoralne, 2026)
Pope Francis has announced that a synod of bishops dedicated to young people will take place in October 2018. The topic of the synod is” “Young people, faith and discerning of calling”. The article “On the way to the synod of bishops dedicated to young people” indicates the meaning of the proposed subject for the life of the Church. The analysis focuses primarily on the presentation of the Preparatory document announced 13th January 2017 by the Secretariat of synod. This document is to be a kind of a compass setting the further work and preparation for the synod. Some critical remarks have also been made concerning the proposed methodology of the synod proceedings, as well as concerning the Preparatory document.